دراسة نظرية لتحديد عوامل الجسوءة في بلّورة المادة الفيرومغناطيسية ( الحديدية المغنطة ) (Latakia University Journal -Basic Sciences Series, 2014)
تم في هذا العمل تحديد عوامل الجسوءة ( ، ،  ) في بلّورة مادة  فيرومغناطيسية  تدخل في حسابات ثوابت تباين المناحي ( Anisotropy) للبلورات المغناطيسية. علاوةً على ذلك, تم تحديد قيم مجالات   بين متجهة تمغنط البلورة  واتجاه الحقل المغناطيسي المطبق عليها  , التي توافق وجود حالات التوازي  ، وحالات التوازي المضاد   ، وكذلك المجالات المناسبة لعملية القفز المغناطيسي بين الحالتين . This work studies the determination of stiffness factors  , and  in  ferromagnetic crystal which enter into the calculations of anisotrophic constants of ferromagnetic crystal . However , Value intervals of  C3 which coresponds to the existence of parallel states  , and  antiparallel states  between the magnetic crystal vector  and applied magnetic field vector  . In addition , the suitable intervals for the magnetic jumps between two  states have been found.